Emissions analysis of an SI engine with humidified air induction. (August 2018) - Kapusuz, Murat; Cakmak, Abdulvahap; Ozcan, Hakan
Abstract: In this experimental research, the effects of humidified air induction on emissions of an SI engine have been investigated. Experiments have been performed on four-stroke SI engine fuelled with unleaded gasoline at two loads (50 % and 100 %) and four engine speeds (1200, 1400, 1600 and 1800 rpm) for 35 % and 80 % relative humidity. The experiments were first made with 35 % humid air, then the relative humidity of the intake air was increased 80 % with water injection and the same experiments were repeated. Exhaust emissions such as NOx, CO, HC and CO2 were measured and compared for each test condition. The results show that enhancement the relative humidity of the inducted air from 35 % to 80 % reduced the NOx, CO2, CO and HC emissions at full engine load with an improvement in brake thermal efficiency.